EMSQOL-29: Prospective validation of the abbreviated, electronic version of MSQOL-54. (May 2019) - Rosato, Rosalba; Testa, Silvia; Bertolotto, Antonio; Scavelli, Francesco; Giovannetti, Ambra M; Confalonieri, Paolo; Patti, Francesco; Chisari, Clara Grazia; Lugaresi, Alessandra; Pietrolongo, Erika; Grasso, Maria Grazia; Rossi, Ilaria; et al.
Background: We recently devised a shortened version of the 54-item Multiple Sclerosis Quality of Life (MSQOL-54) in paper (MSQOL-29, consisting of 25 items forming 7 subscales and 4 single items, and one filter question for 3 'sexual function' items) and electronic format (eMSQOL-29). Objectives: To prospectively assess eMSQOL-29 psychometric properties, acceptability/equivalence versus MSQOL-29. Methods: Multiple sclerosis (MS) patients ( n  = 623; Expanded Disability Status Scale (EDSS) range 0.0–9.0) completed eMSQOL-29, Hospital Anxiety and Depression Scale, Functional Assessment of MS (FAMS), European Quality of life Five Dimensions-3L, and received EDSS and Symbol Digit Modalities Test (SDMT). Equivalence versus MSQOL-29 was assessed in 242 patients (randomized cross-over design). Results: ' Sexual function' items were filtered out by 273 patients (47%). No multi-item scale had floor effect, while five had ceiling effect. Cronbach's alpha range was 0.88–0.90. Confirmatory factor analysis showed good overall fit and the two-factor solution for composite scores was confirmed. Criterion validity was sub-optimal for 'cognitive function' (vs SDMT, r  = 0.25) and 'social function' (vs FAMS social function, r  = 0.38). eMSQOL-29 equivalence was confirmed and its acceptability was good. Conclusion: eMSQOL-29 showed good internal consistency, factor structure and no floor effect, while most subscales had some ceiling effect. Criterion validity was sub-optimal for two subscales. Equivalence and acceptability were good.